Consumers’ intention to purchase genetically modified soybean products in Malaysia - Son, Welson Chin Vui; Seng, Kelly Wong Kai; Sharifuddin, Juwaidah (2016)
In this study, the main objective is to determine the consumers’ intention to buy the GM soybean products in Malaysia. In order to analyze the consumer intention, the theory of Planned Behavioral Model (hereafter TPB) is employed and a survey with 215 respondents was conducted in Klang Valley, Malaysia. Firstly, the factor analysis is use to identify the possible variables influence the consumers’ intention to purchase the GM soybean product. Furthermore, the logistic regression is employed to examine the significant relationship between the influence factors to the consumers’ intention to buy. In this study, the result shows that there are 4 main factors that will influence the acceptance of consumer toward GM soybean products which are consumer awareness, perceive values, knowledge and subjective norms. Furthermore, the factor score for these four identified factors are applied into the binary logistic regression and to examine the significant factors influence the probability of consumer’s intention on purchase the GM soybean products. The binary logistic result shows that consumers’ positive awareness, perceive values, and gender have statistically significant at 5% significance level. This indicates that there is enough statistical evidence to support that the consumers’ intention to purchase the GM soybean products can be influenced by the three important factors, i.e. consumers’ positive awareness; positive perceive values on the GM products, and the respondents’ gender.